Cannabis y riesgo cardiovascular en adultos jóvenes del Cantón Balsas, de la provincia de El Oro - Narda Noelia Orellana Cuenca (2023)
The side effect of cannabis use in the young adult population is increased blood pressure, without affecting aspects such as total cholesterol, HDL cholesterol, and cardiovascular risk. The purpose of this research was to identify degrees of arterial hypertension, total cholesterol and HDL cholesterol; determine the probability of suffering a cardiovascular event in the next 10 years according to sex and age group, as well as estimate its correlation in people who consume and do not consume cannabis, in the city of Balsas, El Oro province. A comparative quantitative, cross-sectional study was carried out with a sample of 40 people, 20 cannabis consumers and 20 non-consumers in whom cardiovascular risk was calculated based on the Framingham’s charts. The results showed that 50% of cannabis consumers manifested some degree of hypertension; while 95% of the non-consumers registered pressures within the optimal - high normal ranges; in terms of total cholesterol levels, the consumers were in the normal range more frequently than those who did not consume cannabis, 75% vs. 70% respectively; regarding HDL cholesterol, it was found that consumers who were within normal values represented a lower amount than in non-consumers, 95% vs. 100%. Finally, cardiovascular risk was low in all the participants. Once the variables were correlated, it was shown that there is no statistically significant relationship